Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 203941 by Panav last updated on 02/Feb/24

If a^(2 ) −a+2=0 and x^2 =a^6 +2a^4 +a^2  then find x?  IIT−JEE based question. Find sol^n .

Ifa2a+2=0andx2=a6+2a4+a2thenfindx?IITJEEbasedquestion.Findsoln.

Answered by Rasheed.Sindhi last updated on 02/Feb/24

If a^(2 ) −a+2=0 and x^2 =a^6 +2a^4 +a^2  then find x?  a^(2 ) −a+2=0⇒a^2 =a−2  ⇒a^3 =a^2 −2a=(a−2)−2a=−a−2  ⇒a^4 =−a^2 −2a=−(a−2)−2a=−3a+2  ⇒a^5 =−3a^2 +2a=−3(a−2)+2a=−a+6  ⇒a^6 =−a^2 +6a=−(a−2)+6a=5a+2    x^2 =a^6 +2a^4 +a^2          =(5a+2)+2(−3a+2)+(a−2)         =4  x=±2

Ifa2a+2=0andx2=a6+2a4+a2thenfindx?a2a+2=0a2=a2a3=a22a=(a2)2a=a2a4=a22a=(a2)2a=3a+2a5=3a2+2a=3(a2)+2a=a+6a6=a2+6a=(a2)+6a=5a+2x2=a6+2a4+a2=(5a+2)+2(3a+2)+(a2)=4x=±2

Commented by siyathokoza last updated on 06/Feb/24

If a^(2 ) −a+2=0 and x^2 =a^6 +2a^4 +a^2  then find x?  a^(2 ) −a+2=0⇒a^2 =a−2  ⇒a^3 =a^2 −2a=(a−2)−2a=−a−2  ⇒a^4 =−a^2 −2a=−(a−2)−2a=−3a+2  ⇒a^5 =−3a^2 +2a=−3(a−2)+2a=−a+6  ⇒a^6 =−a^2 +6a=−(a−2)+6a=5a+2    x^2 =a^6 +2a^4 +a^2          =(5a+2)+2(−3a+2)+(a−2)         =4  x=±2   BY:siythokoza ngema...(NSQ)

Ifa2a+2=0andx2=a6+2a4+a2thenfindx?a2a+2=0a2=a2a3=a22a=(a2)2a=a2a4=a22a=(a2)2a=3a+2a5=3a2+2a=3(a2)+2a=a+6a6=a2+6a=(a2)+6a=5a+2x2=a6+2a4+a2=(5a+2)+2(3a+2)+(a2)=4x=±2BY:siythokozangema...(NSQ)

Answered by Rasheed.Sindhi last updated on 02/Feb/24

If a^(2 ) −a+2=0 and x^2 =a^6 +2a^4 +a^2  then find x?  a^(2 ) −a+2=0⇒a^2 =a−2     x^2 =a^2 (a^4 +2a^2 +1)       =a^2 (a^2 +1)^2   x=±a(a^2 +1)     =±a(a−2+1)     =±a(a−1)     =±(a^2 −a)     =±(a−2−a)    =∓2  x=±2

Ifa2a+2=0andx2=a6+2a4+a2thenfindx?a2a+2=0a2=a2x2=a2(a4+2a2+1)=a2(a2+1)2x=±a(a2+1)=±a(a2+1)=±a(a1)=±(a2a)=±(a2a)=2x=±2

Commented by Panav last updated on 10/Feb/24

Correct

Correct

Answered by Rasheed.Sindhi last updated on 02/Feb/24

If a^(2 ) −a+2=0 and x^2 =a^6 +2a^4 +a^2  then find x?  a^(2 ) −a+2=0⇒ { ((2=a−a^2 )),((a^2 =a−2)) :}     x^2 =a^6 +2a^4 +a^2 =a^6 +(a−a^2 )a^4 +a^2       =a^6 +a^5 −a^6 +a^2 =a^2 (a^3 +1)     =a^2 ( a(a−2)+1 )     =a^2 (a^2 −2a+1)  x =±a(a−1)      =±(a^2 −a)      =±(a−2−a)      =∓2  x=±2

Ifa2a+2=0andx2=a6+2a4+a2thenfindx?a2a+2=0{2=aa2a2=a2x2=a6+2a4+a2=a6+(aa2)a4+a2=a6+a5a6+a2=a2(a3+1)=a2(a(a2)+1)=a2(a22a+1)x=±a(a1)=±(a2a)=±(a2a)=2x=±2

Answered by deleteduser1 last updated on 02/Feb/24

a^2 =a−2⇒a^4 =a^2 −4a+4=a^2 −a+2−3a+2=2−3a  ⇒x^2 =a^6 +4−6a+a−2=a^6 −5a+2  a^3 =a^2 −2a=a^2 −a+2−a−2=−2−a  ⇒a^6 =a^2 +4a+4=a^2 −a+2+5a+2=5a+2  ⇒x^2 =5a+2−5a+2=4⇒x=+_− 2

a2=a2a4=a24a+4=a2a+23a+2=23ax2=a6+46a+a2=a65a+2a3=a22a=a2a+2a2=2aa6=a2+4a+4=a2a+2+5a+2=5a+2x2=5a+25a+2=4x=+2

Answered by esmaeil last updated on 02/Feb/24

x^2 =(a^3 +a)^2 →x=a(a^2 +1)=^(a^2 −a+2) a(a−1)=  a=((1±i(√7))/2)→a(a−1)=x  (((1+i(√7))/2))(((i(√7)−1)/2))=((−7−1)/4)=−2=x  (((1−i(√7))/2))(((−i(√7)−1)/2))=(8/4)=2=x

x2=(a3+a)2x=a(a2+1)=a2a+2a(a1)=a=1±i72a(a1)=x(1+i72)(i712)=714=2=x(1i72)(i712)=84=2=x

Terms of Service

Privacy Policy

Contact: info@tinkutara.com